Estimating safety factor for femoral plates subjected to in vivo loads - Bologna Federico Andrea; Audenino Alberto Luigi; Terzini Mara (Current Directions in Biomedical Engineering)
Fatigue behaviour is a crucial aspect of mandatory mechanical tests for regulatory purposes, aimed at determining the load at which the bone plate withstands under a specific number of cycles, known as the runout condition. However, current test standards, such as ASTM F382, provide setup configurations without explicit guidelines on required fatigue strength. The determination of the minimum level of in vivo performance that the plate must fulfil remains an open issue, which is frequently addressed by the direct comparison with predicate devices. To address this gap, this study proposes an in silico framework to estimate maximum stress on implanted femoral plates for comparison with four-point bending tests described in the ASTM standard, deriving appropriate safety factors. As case studies, three femoral plates were assessed, and results showed safety factors above 1.1, indicating the reliability of the implanted plates.